Costume- as to health - Brady, Hope (My University, 1898)
Introduction: It is said that the subject of dress is the one nearest woman’s heart, that she thinks only of dress; but is she not letting others think for her? Is it not the thoughts of others by which she is grinded in her dress? To these others then, must we lay the blame of leading her astray in her choice of garments.
Citation: Brady, Hope. Costume- as to health. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Dress; Garments; Women; Health; Theses; Manuscripts (documents)